If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 10 = 9 Reorder the terms: 10 + 3y = 9 Solving 10 + 3y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3y = 9 + -10 Combine like terms: 10 + -10 = 0 0 + 3y = 9 + -10 3y = 9 + -10 Combine like terms: 9 + -10 = -1 3y = -1 Divide each side by '3'. y = -0.3333333333 Simplifying y = -0.3333333333
| 3m-4=2m-13 | | 41+8z=-z^2 | | 8x+12=100 | | b-3+3b=36 | | 3y+7=9 | | 4(y+2)=5(y-5) | | 6x-10=-18x-4 | | 3x^2-15x+45=0 | | 2(-2+x)-1(x-4)=0 | | (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= |